Analisis Tingkat Autisme pada Anak Berkebutuhan Khusus Menggunakan Childhood Autism Rating Scale (CARS) di Sekolah Luar Biasa Taman Pendidikan Islam Medan - Sri Bunga Syafitri; Rahmatrisilvia; Nabila Azzahra; Nopenri Lubis; Arhe Aan Yesa Purba (Medan Resource Center, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by persistent impairments in communication, social interaction, and behavioral functioning, requiring accurate assessment to inform appropriate educational and therapeutic interventions. This study investigates the severity of autism among children with special needs at Taman Pendidikan Islam Special School Medan using the Childhood Autism Rating Scale (CARS). The study employed a descriptive quantitative design with a total sampling technique involving 32 children aged 5–18 years diagnosed with Autism Spectrum Disorder. Data were collected through structured observations and CARS assessments administered by trained special education teachers. The findings revealed that 9.4% of participants were classified as non-autistic, 50.0% as having mild-to-moderate autism, and 40.6% as having severe autism. The highest mean scores were identified in the CARS domains of imitation (M = 2.91), adaptation to change (M = 2.84), and visual response (M = 2.78), indicating substantial developmental challenges in these areas. The study concludes that most students require intensive, individualized, and structured educational and therapeutic interventions, highlighting the importance of CARS as a reliable assessment tool for designing adaptive intervention programs that address students' specific developmental needs.